(untitled) (Revista Española de Fisiología, 1971)
Action of three /3-sympathomimetic drugs on the uterine basal tonus is studied in vivo with an original and improved method. Our method permits the simultaneus record of both isometric and isotonic uterine contractions. Administration of crecent doses of /?-sympathomimetics induces a fall of uterine basal tonus in relationship with dose. Respect to maximum effect isoprenaline (isopreterenol) is the most uterine tonus relaxant, orciprenaline and Th-1165a are potents 70 and 60 % respectively. The ED 50 % of isoprenaline is little low than Th-1165a but ED 50 % of orcipre naline is about five fold higher. Decrease of basal tonus is independent of uterine activity low. Isotonic record shows a length increase of uterine muscle. Threshold phenomen is showed with three drugs but it is most evident with isoprenaline.